ナンキョク ヤガイ チョウサ ニ オケル タイヨウコウ ハツデン システム ノ カツヨウ ダイ50ジ ニホン ナンキョク チイキ カンソクタイ セール・ロンダーネサンチ チガク チョウサタイ ノ レイ - 亀井, 淳志; カメイ, アツシ; 阿部, 幹雄; アベ, ミキオ; 志村, 俊昭; シムラ, トシアキ; 柚原, 雅樹; ユハラ, マサキ; 大和田, 正明; オオワダ, マサアキ; 束田, 和弘; ツカダ, カズヒロ; et al. (2009)
P(論文) 第50次日本南極地域観測隊(第50次隊)夏隊のセール・ロンダーネ山地地学調査隊は67日間におよぶ野外調査を行い,その間に必要な電力を太陽光発電で賄った.今回使用した太陽光発電システム(出力電圧約12 V)の1日あたりの発電量は6724 Ahであった.そして,この調査によって以下の3つの重要なことが明らかとなった.1)南極での野外調査生活に必要な電力は太陽光発電システムにより得ることが可能である.2)最大出力電流2.3 Aの太陽パネルは1日あたり910 Ahを発電する.3)夏季の南極は白夜のために日照が途絶える事はないが,当山地では0000 LTから0500 LT (昭和基地時刻) の間に太陽光発電ができない. The field party in the Sør Rondane Mountains, a part of the summer party of the 50th Japanese Antarctic Research Expedition (JARE-50), performed as outdoor survey using a solar-electric system for field camping over a period of 67 days. The total amount of power generation (output: ca 12V) varied from 67 to 24 Ah/day. We obtained three important conclusions: 1) Electric power is sufficiently supplied from the solar-electric system in the field camp. 2) The solar panel (maximum output 2.3 A) used by JARE-50 generates 9-10Ah/day. 3) The solar panel did not produce electric power during the midnight sun (0000-0500 LT; the time for Showa Station area) in the Antarctic summer season. departmental bulletin paper